Low rate of long-lasting remissions after successful treatment of immune thrombocytopenic purpura with rituximab - Schweizer, Christof; Reu, Frederic; Ho, Anthony Dick; Hensel, Manfred (Annals of hematology, 2007)
Idiopathic thrombocytopenic purpura (ITP), also known as immune thrombocytopenic purpura, is thought to be caused primarily by the production of autoantibodies directed against platelet surface glycoproteins. Treatment of an acute ITP episode can be difficult, and relapses are common. Recent studies have shown that the anti-CD20 antibody rituximab is effective in the treatment of relapsed and refractory patients. We report the results of a retrospective analysis of rituximab treatment in 14 patients with immune thrombocytopenic purpura. Nine of these patients had a refractory disease, and five patients had a relapse of the thrombocytopenia. The median time since last treatment was 10 days (range 1-470 days). All patients were previously treated with one to seven different regimens, and four had undergone splenectomy. Rituximab was administered at the standard dose of 375 mg/m2 once per week with a median of 4 infusions (range 2-4). The overall response rate was 64%; 7 of 14 patients (50%) achieved a complete remission (platelet levels > 100 × 109/l), 2 of 14 patients (14%) had a partial remission (platelets > 50 × 109/l), and 5 patients did not respond. The median time to response was 2 weeks (range 1-4) after the first infusion. Responding patients stayed in remission for a median period of 8 weeks (range 10 days-36 months). Three patients (21%) remained in remission after 26 to 156 weeks of follow-up. All of the four splenectomized patients achieved a complete remission after rituximab therapy, and two of them are still in remission after 26 and 156 weeks observation. Our data confirm that rituximab is well tolerated and effective in refractory and relapsed immune thrombocytopenias; however, response duration was short, and only about one fifth of our patients enjoyed a long-lasting remission.